Supporting the tutor in a tutor-tutee adaptive educational system - Lahart, Orla (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2009)
Adaptive educational systems have been successful in providing personalised support in a myriad of domains (Melias & Siekmann, 2004). To provide such support, the adaptive educational system builds an internal representation of the user by analysing the user’s behaviour including their knowledge and traits (Brusilovsky & Peylo, 2003). The resulting model is used to adapt the learning environment to that which best suits the individual learner. Furthermore, within a tutoring environment where there are two users, tutor and tutee, working collaboratively to reach a common goal, there may be a need to provide personalised domain support for both users. One particular environment where there may be a need for such a system is home tutoring. Despite the large body of research, which suggests a high correlation between home tutoring and a child’s academic success (Greenwood & Hickman, 1991; Dornbusch & Ritter, 1988), parental involvement in learning activities in the home may not occur spontaneously due to self-believed lack of ability, knowledge and skills (HooverDempsey & Sandler, 1995). However, research indicates the benefit of supporting the tutor in the development of tutoring strategies (Cotton & Savard, 1982). Hence, the need for the development of an adaptive educational system, which supports both, tutor (parent) and tutee (child) during the home tutoring process. Such a system could in particular be of most benefit in supporting the tutor in the development of tutoring strategies. There are many unresolved issues in developing such an adaptive educational systems. Research questions still outstanding include: (1) how can an adaptive engine simultaneously support dual users (tutor and tutee) (2) what is the appropriate educational theory from which to elicit a set of rules, which define tutoring best practice and (3) what is an appropriate basis for adapting to the needs of the tutor and tutee? This thesis describes how the Parent and Child Tutor (P.A.C.T.) adaptive educational system addresses these challenges. Firstly, the thesis describes how P.A.C.T.’s architecture differs from that of a traditional adaptive educational system in an endeavour to provide dual user adaptivity. Secondly, the thesis describes how Talent Education philosophy (Suzuki, 1986) informs a set of tutoring rules, which define tutoring best practice. Thirdly, the thesis describes how self-efficacy (person’s belief in their ability to accomplish a particular task) can be used to determine the appropriate level of support required by the tutor and how affect (the emotional state) can be used to determine the type of support required by the tutee. v Empirical studies were conducted to explore the effect of using an adaptive educational system to support the home tutoring process in the domains of Suzuki violin and mathematics. In particular, these studies explored the effect of P.A.C.T. on parents’ (1) self-efficacy (2) knowledge and (3) perception of their role as home tutor. In addition, studies investigated the effect of providing affective support for the child throughout the home tutoring process. Results suggest that P.A.C.T. may be of benefit in increasing parental self-efficacy and parents’ knowledge of home tutoring skills. They also indicate that P.A.C.T. may have a positive effect on parents’ perception of their role as home tutor. Results also suggest that adapting the tutoring process based on the affective needs of the child may have a positive effect on the home tutoring process. In summary the main contributions of this thesis are: • The design and development of an architecture, which supports dual user adaptivity in the domain of home tutoring. • The articulation and development of a set of novel tutoring rules based on Talent Education philosophy, which defines tutoring best practice. • Empirical evidence, which indicates the effectiveness of adaptive strategies based on self-efficacy in supporting the parent as tutor and strategies based on affect in supporting the child as tutee.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin